Synthesis and characterization of Fe–ZrO2 metal matrix composites. (July 2014) - Jha, Pushkar; Gupta, Pallav; Kumar, Devendra; Parkash, Om
This investigation reports the phase, microstructure and hardness of ZrO2 -reinforced iron-based metal matrix composites synthesized by powder metallurgy. The process involved the preparation of homogeneous mixture of electrolytic iron powder with different weight percentages (5%, 10%, 20% and 30%) of ZrO2 by milling, compaction in the form of rod and sintering in the temperature range of 900–1100℃ for 1–3 h in argon atmosphere. The sintered samples were subjected to X-ray diffraction for phase analysis and to scanning electron microscopy for microstructure evaluation. The X-ray diffraction and scanning electron microscopy results show the presence of Fe, ZrO2 and Zr6 Fe3 O phases. This Zr6 Fe3 O phase is formed due to reactive sintering. From these studies it is concluded that two types of sintering are involved: (a) solid state sintering between Fe particles and (b) reactive sintering with the formation of iron zirconium oxide. Density and hardness of composite specimens were found to depend on fraction of ZrO2, the nature of sintering and the formation of Zr6 Fe3 O phases.